2013
DOI: 10.1096/fj.13-230201
|View full text |Cite
|
Sign up to set email alerts
|

The noninflammatory role of high mobility group box 1/toll‐like receptor 2 axis in the self‐renewal of mammary cancer stem cells

Abstract: Cancer stem cells (CSCs) are responsible for tumor progression, metastases, resistance to therapy, and tumor recurrence. Therefore, the identification of molecules involved in CSC self-renewal is a necessary step toward more effective therapies. To this aim, through the transcription profiling of the murine ErbB2(+) tumor cell line TUBO vs. derived CSC-enriched mammospheres, Toll-like receptor 2 (TLR2) was identified as 2-fold overexpressed in CSCs, as confirmed by qPCR and cytofluorimetric analysis. TLR2 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 42 publications
6
101
0
Order By: Relevance
“…We previously showed that TLR2/MyD88 signaling in tumor cells promotes gastric tumorigenesis in gp130 F/F mice (19,28). Consistent with these findings, it has been shown that TLR2 signaling in cancer cells plays a tumor-promoting role through the enhancement of stemness (23,24). Moreover, the epithelial cell-specific deletion of Myd88 was observed to suppress intestinal tumorigenesis in Apc Min mice (16).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…We previously showed that TLR2/MyD88 signaling in tumor cells promotes gastric tumorigenesis in gp130 F/F mice (19,28). Consistent with these findings, it has been shown that TLR2 signaling in cancer cells plays a tumor-promoting role through the enhancement of stemness (23,24). Moreover, the epithelial cell-specific deletion of Myd88 was observed to suppress intestinal tumorigenesis in Apc Min mice (16).…”
Section: Discussionsupporting
confidence: 57%
“…13,42). It has been reported that TLR2/4 recognize high-mobility group box 1 and extracellular matrix proteoglycan versican that are produced by cancer cells (24,43,44). Accordingly, cancer cell-derived ligands as well as infectious agents may We also showed that inflammatory responses induced the expression of TLR2 and CD14 in tumor epithelial cells (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…1A and B, respectively), as has already been observed in previous reports. 22,24 Moreover, tumorspheres showed increased in vitro self-renewal, with respect to TUBO cells in our own experiments. This is demonstrated by the higher number of cell clones generated by tumorspheres in a limiting dilution assay (Fig.…”
Section: Tumorspheres Derived From the Murine Erbb2supporting
confidence: 66%
“…21 Previous data have shown that NK cells selectively kill CSCs derived from human colon carcinoma, 15 melanoma 16 and glioblastoma, 17 in mainly in vitro experiments. We herein describe in vitro and in vivo experiments which validate the NK cell targeting of breast tumor-derived CSCs using CSC-enriched tumorspheres 22 derived from an ErbB-2 C murine breast cancer tumor cell line (TUBO), 23 and murine and human triple negative breast cancer (TNBC) cell lines.…”
mentioning
confidence: 99%